STUDI KELARUTAN PROPAGERMANIUM DENGAN METODE KROMATOGRAFI CAIR KINERJA TINGGI - Putranti, Widyasari; Martodihardjo, Suwaldi; Lukitaningsih, Endang (Universitas Ahmad Dahlan, 2014)
Propagermanium, a synthetic organic compound of germanium is known as Î²- or biscarboxyethylgermaniumsesquioxide or Ge-132. It is found in some plants such as shelf fungus,ginseng, garlic, and Aloe vera. Ge-132 plays an important role for the pharmacological effectsof the plants. The solubility of propagermanium at a certain pH is not exactly known yet. Untilnow, the analytical methods for the analysis of Ge-132 so far have the shortcoming and thepropagermanium as germanium metal in the sample, so that improvement for propagermaniumanalysis was necessary to be conducted, primarily to be used for solubility assay. This studyaims to determine the effects of pH on the propagermanium solubility using HPLC method foranalysis. The results showed that validation parameters for analysis by using HPLC method e.iaccuracy, precision, and linearity, have met to the quantitative analysis requirements. Increasingthe pH causes increasing the solubility of propagermanium in the pH range of 3.0-3.6. Thesolubility result was 9.8514; 10.4204; 12.5446 mg/mL on pH 3.0; 3.3; 3.6.